2023
DOI: 10.3390/healthcare11111553
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in Immersive Virtual Reality: A Scoping Review

Abstract: Physical activity has benefits for health, but many adolescents are inactive. However, video games such as Immersive Virtual Reality (IVR) have grown in popularity as a leisure activity among young people, allowing them to manipulate objects in virtual environments increasing the practice of physical activity. The evidence indicates that the interest in physical activity through IVR is greater than in traditional methods, and different experiences have been reported. However, few studies indicate the sample ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Although many recent studies have assessed PA intensity in VR [13,15,16,19,33,34], few of them addressed exercise using an omnidirectional treadmill. This is probably due to the fact that this type of equipment is still relatively expensive and not widely available.…”
Section: Discussionmentioning
confidence: 99%
“…Although many recent studies have assessed PA intensity in VR [13,15,16,19,33,34], few of them addressed exercise using an omnidirectional treadmill. This is probably due to the fact that this type of equipment is still relatively expensive and not widely available.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, we posit that these results were a product of a decrease in perceived exertion as well as the adaptive resistance mechanisms within the IVR machine. A benefit of virtual reality within the realm of exercise is that a heightened enjoyment may attenuate perceived exertion, which ultimately pushes individuals to work closer to fatigue (Giakoni-Ramírez et al, 2023). In the past, our laboratory has observed high rates of workout satisfaction in conjunction with significant differences in rates of perceived exertion when comparing IVR exergaming to traditional, cablebased strength training (Hu et al, 2021;Mologne et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…While some of these works focus on specific subtypes or use cases of XR exergames, no work has yet provided an up-to-date overview of this rapidly evolving domain. Some reviews focused on general physical activity, not particularly on exergames (e.g., [79,184]). Other reviews covered non-immersive "VR" exergames (e.g., [36,45,49]) and examined their health-related outcomes (e.g., [49,141,165]).…”
Section: Existing Literature Reviews and Taxonomiesmentioning
confidence: 99%
“…Kappen et al [110] identified various focuses of non-immersive exergames (e.g., cognitive training) for older adults, which we incorporated in the goal dimension of our taxonomy. Lastly, only a few papers considered the intersection of XR technology and physical activity (e.g., [79,184]). Odenigbo et al [184] reviewed 39 VR, AR, and MR physical activity interventions and showed that most of them included exergaming.…”
Section: Existing Literature Reviews and Taxonomiesmentioning
confidence: 99%